Deconstructing Taylor Swift's Song Entitled “The Man”: Exploring Gender Issues Through The Lyrics - Bunga Putri Maulia (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research discusses the song entitled "The Man" by Taylor Swift from a gender perspective. This song describes women's views on how their lives would be different if they were men. The aim of this research is to determine the specific representation of gender equality in Taylor Swift's song "The Man". This type of research is content analysis with a deconstruction approach; we will delve into the lyrics of this song and analyze how Taylor Swift highlights gender inequality and stereotypes that are still widespread in society. The results show that in her song entitled "The Man", Taylor Swift describes how stereotypes still exist in society regarding gender inequality. The gender equality that Taylor Swift advocates through her songs includes many things such as; freedom to choose a lifestyle, freedom to be a leader, freedom to work without discrimination from the social environment and several other freedoms that are difficult for women to obtain.